Inhibition of soluble epoxide hydrolase in endotoxin induced pig lung injury - Larsson, Niklas; McReynolds, Cindy B.; Hwang, Sung Hee; Wan, Debin; Yang, Jun; Lindberg, Richard; Lehtipalo, Stefan; Claesson, Jonas; Liljeström, Amanda Irgum; Lind, Alicia; Brolin, Anders; Mettävainio, Martin Isaksson; et al. (Frontiers in Pharmacology, 2025)
Pharmacological inhibition of soluble epoxide hydrolase has been shown to attenuate lung injury development in rodents exposed to bacterial lipopolysaccharide. To investigate if these effects can be reproduced in larger animals, we tested soluble epoxide hydrolase (sEH) inhibition using an sEH inhibitor 1-adamantanyl-3-5-[2-(ethylethoxy)ethoxy]pentylurea (AEPU) in a porcine model of lipopolysaccharide-induced acute lung injury. AEPU was selected from 23 sEH inhibitors based on IC50 values and metabolic stability profiles established by a fluorescent based activity assay and porcine liver microsomal test, respectively. Hydrolysis of fatty acid epoxides to their corresponding diols is catalyzed by sEH. Inhibition of sEH reduces this conversion, leading to an accumulation of epoxides relative to diols. Hence, AEPU-treated subjects (n = 9) showed metabolic signs of effective in vivo inhibition of the target enzyme reflected in an increased epoxide/diol ratio of 12 (13)-epoxyoctadecenoic acid to 12,13-dihydroxyoctadecenoic acid compared to placebo-treated controls (p = 0.026). However, there was no difference in lung injury development or survival in subjects treated with the rapidly metabolized AEPU compared to placebo-treated controls (n = 10). In conclusion, administration of the soluble epoxide hydrolase inhibitor AEPU did not attenuate endotoxin induced lung injury with lipopolysaccharide in pigs under the severe conditions tested here.